Study on the use of long lasting insecticidal nanonet jacket (LLINJ) for malaria vector control - อ่วมอ่อง บุญเสริม; เสวะนา จิราภรณ์; สินาคม บุษราคัม; ยงชัยตระกูล ศิริพร; หมื่นราษฏร์ ยุทธพงศ์ (Disease Control Journal, 2018)
The research on the effectiveness of a long lasting insecticidal nano netting jacket (LLINJ) against mosquito bites was conducted in Surat Thani Province. Deltamethrin treated jackets and locally made nano netting were used to protect against mosquito bites to prevent outdoor malaria transmission and to compare levels of man-vector contact density, through landing catches, between LLINJ and non-LLINJ wearing groups of entomologists. The residual effects of deltamethrin on the nano netting of LLINJs under laboratory and field conditions were investigated. Furthermore, the local malaria vectors were tested against deltamethrin and other insecticides to determine their susceptibility status. Measurement was done for protective ability of LLINJs toward a number of infected malaria cases in the study area. Results showed 71.67% reduction in the number of Anopheles mosquito landings in the LLINJ wearing group compared with the non-LLINJ wearing group , which was a statistically significant difference with p<0.05 (2= 37.608, p=0.000). There was a significant reduction of 74.42% in the number of local malaria vector, Anopheles minimus, landing in the LLINJ wearing group compared with the non-LLINJ wearing group with p<0.05 (2= 31.065, p=0.000). Despite the number of An. dirus collected in this study being low, its number in the LLINJ wearing group was not significantly lower than that of the non-LLINJ wearing group (2= 3.210, p=0.668). The residual effect of deltamethrin treatment on LLINJ at a dose of 60 mg/m2 in 18 months was effective under both laboratory and field conditions. It was also found that wildly caught An. minimus was susceptible to deltamethrin as well as other alternative pyrethriods, such as permethrin, bifenthrin, alphacypermethrin, including carbamate insecticide, propoxur. Study result provides useful information for an alternative measure to control outdoor malaria transmission. Further well-designed large-scale studies are needed to determine the impact for the use of LLINJ as well as encouraging large scale production of LLINJ.